Isolation, Identification, and Antibacterial Testing of Essential Oil from Green Betel Leaf (Piper Betle L.) Using Well Diffusion Method - Enny Fachriyah; Hafizdah Fadillah; Purbowatiningrum Ria Sarjono; Ismiyarto Ismiyarto (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
Green betel leaves have been traditionally employed within communities for various medicinal purposes, owing to their rich composition. These leaves are endowed with secondary metabolites encompassing flavonoids, phenols, saponins, and essential oils. Notably, the essential oils within green betel leaves possess a spectrum of biological properties, including antioxidant, antifungal, antidiabetic, anti-inflammatory, antibacterial, antitumor, anti-Alzheimer's, and anti-carcinogenic activities. In this study, the essential oil from green betel leaf collected from Klaten, Central Java, Indonesia, was isolated using water-steam distillation. The components of this isolate were identified using GC-MS analysis. Antibacterial activity was assessed against Staphylococcus epidermidis ATCC 12228 (S. epidermidis) and Escherichia coli (E. coli) using the well-diffusion method at various concentrations (25%, 50%, 75%, 90%, and 100%). Chloramphenicol served as the positive control, while a solution of Tween 20 in distilled water used as the negative control. The essential oil derived from green betel leaves exhibited a brownish-yellow color, possessed a distinctive betel aroma, and had a concentration of 0.21% v/w, a refractive index of 1.5001, and a specific gravity of 0.961 g/mL. The GC-MS analysis revealed the presence of 44 components, with the five most abundant constituents being acetyl chavicol (20.65%), germacrene- D (11.55%), eugenol (8.94%), trans-caryophyllene (7.92%), and chavicol (5.74%). Regarding antibacterial activity, the isolate demonstrated strong activity against S. epidermidis ATCC 12228 at a concentration of 75%, yielding an inhibition zone diameter of 12.33 mm. Similarly, it exhibited strong activity against E. coli at a concentration of 90%, resulting in an inhibition zone diameter of 12.67 mm.